APLIKASI SIMULASI PROSEDUR PENERBITAN SIM BERBASIS MULTIMEDIA - Afrizal -; Ariana Anggun Meilani (JURNAL AKADEMIKA)
The author designed the application procedure sim based multimedia publishing in jambi police using software adobe flash cs3 and adobe photoshop cs6 required in sim simulation application composed of the form menu opening and main menu.Main menu consisiting of driving license profile,driving license application guidance, driving license help road map, administrator is driving license,and driving license publication mechanism. application procedure sim guide provides information about the movements and procedures of the good and true procedure sim.obviously the author expects this application could be beneficial for the users to learn about procedure sim.